Congenital adrenal hyperplasia presented with bilateral testicular tumor: a case report - Abazar Akbarzadeh Pasha; Hamid Shafi; Mohammad Teimorian; Ghasem Rostami; Khatereh Nasirimehr; Emadoddin Moudi (Babol University of Medical Sciences, 2021)
Background: Congenital adrenal hyperplasia (CAH) refers to group of congenital diseases resulting from impaired adrenal steroidogenesis, and its most common cause is 21-hydroxylase deficiency. Testicular adrenal residual tumor (TART) is one of the major complications of CAH, possibly resulting from ectopic remnants of intra-testicular adrenal tissue which is stimulated by excessive secretion of adrenocorticotropic hormone (ACTH). This tumor can be misdiagnosed as Leydig cell tumor (LCT) in these people. Case Presentation: The patient we are presenting is a 20-year-old man with a history of precocious puberty and a height below 3% of the population who underwent radical left testicular orchiectomy with a complaint of bilateral testicular mass, which is reported LCT in the pathology report. In preoperative imaging examinations, bilateral adrenal hyperplasia is observed. In hormonal examinations, the patient is diagnosed with CAH and has been treated with corticosteroids for one year. Conclusion: In patients who present with bilateral testicular mass, it is the best image by abdominopelvic CT scan before surgery to detect CAH.